Adherence to pharmacotherapy improves school performance in children with rhinitis and asthma (2018)
ABSTRACT: Background Adherence to pharmacotherapy reduces symptoms of asthma and rhinitis, however, little is known of its impact on school performance. Objective To evaluate the impact of pharmacotherapy in absenteeism and school performance in a child population. Methods A cross-sectional study, carried out in eight schools. All participants and their parents were given a questionnaire assessing parameters related to respiratory diseases and pharmacotherapy. Data on school performance was obtained from the academic history of each child who participated in the study. Adherence to pharmacotherapy was classified as a correct use of therapy for more than five days per week. Results 1109 children agreed to participate. Students were divided into two groups: symptomatic (36%) and asymptomatic (63%). The symptomatic group had a higher frequency of school absenteeism (1 vs. 3.1days/year/patient p<0.01) and lower academic performance (failed: 20% vs. 33% p<0.01). After dividing the symptomatic group between adherents and non-adherents to the pharmacotherapy, the group of adherents had a similar school performance to the asymptomatic group and it was significantly different from the no-adherent group. Conclusion Respiratory symptoms are associated with poor school performance and with an increase in school absenteeism, but adherence to pharmacotherapy can reduce these negative impacts in children.